IMPROVING ENGLISH VOCABULARY BY USING TOTAL PHYSICAL RESPONSE (TPR) METHOD TO THE FIFTH GRADE STUDENTS OF SDN PASIRKALIKI 1 CIMAHI - Hidayat, Irfan; Suprijadi, Dasep; Inayah, Ratih (IKIP Siliwangi, 2018)
The objective of this research entitled “IMPROVING ENGLISH VOCABULARY BY USING TOTAL PHYSICAL RESPONSE (TPR) METHOD TO THE FIFTH GRADE STUDENTS OF SDN PASIRKALIKI 1 CIMAHI” was to find out whether or not teaching English Vocabulary using Total Physical Response Method was effective to improve the students’ vocabulary ability. The research used quantitative method and one group pretest-posttest design. The population of this research was 31 of the fifth grade elementary school while the sample was entire population. They are consisted of 31 students. The data of this research were collected by giving pretest and posttest to the subject. The collected data were analyzed by using t-test formula. The results of the data analysis showed that: the mean score of pretest was 44.61, the mean score of posttest was 44.83, the tobs was 2.442, the tcritical value at the significance level 0.05 with degree of freedom (df) 30 was 2.042. Based on the data analysis above, the alternative hypothesis was accepted because the tobs was higher than t critical (2.442>2.042). It also meant that improving English vocabulary using Total Physical Response Method was effective to improve the students’ vocabulary ability. Keywords: Vocabulary, Total Physical Response Method